Eksplorasi Faktor-Faktor Penentu Niat Kepatuhan Pengobatan pada Pasien Diabetes Melitus Tipe 2: Studi dengan Pendekatan Theory of Planned Behavior pada Masyarakat Jawa - Fransiska Indah Pratiwi; Aris Widayati; Pramitha Esha Nirmala Dewi (Jurnal Ilmiah Medicamento, 2026)
Background: Diabetes mellitus (DM) requires long-term therapy, which may reduce patients’ adherence to medication and ultimately lead to treatment failure.Objective: This study aimed to analyze factors influencing medication adherence intention among patients with type 2 diabetes mellitus (T2DM) based on the Theory of Planned Behavior (TPB).Methods: An analytical observational study with a cross-sectional design was conducted among patients diagnosed with T2DM in Purworejo Regency, Central Java. Data was collected using a structured questionnaire and analyzed using binary logistic regression in SPSS version 25. A total of 382 respondents were included in the analysis.Results: Most participants were female, aged 55–65 years, employed, and had an elementary school education or equivalent. The proportion of respondents with high medication adherence intention was 85.9%. Attitude, subjective norm, and perceived behavioral control jointly explained 53.6% of the variance in medication adherence intention. Among these variables, subjective norm demonstrated the strongest association with adherence intention (OR = 197.019; p < 0.001).Conclusion: These findings suggest that social influence, particularly encouragement and support from family members and healthcare providers, plays a dominant role in shaping medication adherence intention within a collectivist socio-cultural setting. Integrating culturally sensitive, family-centered approaches into diabetes management programs may therefore strengthen adherence intention and improve long-term treatment outcomes among patients with T2DM.